Culture-dependent PCR-DGGE-based fingerprinting to trace fishing origin or storage history of gilthead seabream. (December 2021) - Bikouli, Vasiliki C.; Doulgeraki, Agapi I.; Skandamis, Panagiotis N.
Abstract: Fish is among the most perishable foods, with spoilage symptoms associated with undesirable growth of microorganisms to unacceptable levels. In the case of seabream, Pseudomonas and Shewanella species are established as the main spoilage organisms. The aim of the present work was to assess gilthead seabreams freshness based on quantitative and qualitative (genetic fingerprinting) microbiological data, assuming that the presence of specific microorganisms, can be used as a potential (taxa) marker of freshness, fishing origin as well as of whether fish has been frozen or not. Freshly caught fish ( max . 8 h after catching) from 4 different Greek sea areas (i.e. Euboea, Saronikos, Argolida and Phthiotis) were analyzed with classical microbiological methods before and during storage at 0 °C for 16 days and at −18 °C for 18 months. The presence of specific microorganisms in fish was monitored using PCR-DGGE. Regarding the classical microbiological analysis, results showed that Pseudomonas, H2 S-producing and non H2 S-producing microorganisms were the dominant microbiota of freshly caught and chilled or frozen stored fish. Enterobacteriaceae community grown on plates incubated at 7 °C for 10 days, was found 1–3 log units higher than those on plates incubated at 37 °C. After 16 days of storage at 0 °C, the dominant populations on freshly caught fish, reached the level of 6–7 log CFU g −1 . DGGE analysis revealed that the microbiota of seabream was influenced by the fishing area and storage conditions. In general, Pseudomonas, Shewanella, Psychrobacter and Arthrobacter were detected in the majority of cases (including fresh fish), regardless of the fishing area, suggesting a significant contribution to fish microbiota. Moreover, genera Stenotrophomonas, Massilia, and Microbacterium were associated with seabream from Saronikos area stored at 0 °C. Similarly, Hafnia was detected on seabream from Euboea, Argolida and Phthiotis stored under the same conditions. Other genera were also associated with the microbiota of seabream caught from Euboea i.e. Moraxella, Rahnella and Sphingobacterium, or Argolida region i.e. Brochothrix, Enhydrobacter, Lactobacillus and Vagococcus . In conclusion, the detection of specific microorganisms could serve as potential indication of freshness, fishing origin and storage history of the fish. However, a follow up metataxonomic culture-independent study could be useful to strengthen and confirm the results of this research. Highlights: Correlation of microbiota with storage conditions & geographical origin of seabreams. Culture-based DGGE fingerprinting to monitor microbiota changes of seabreams. Pseudomonas, Shewanella, Psychrobacter & Arthrobacter belong to fish core microbiota. Specific bacteria could serve as indicators of origin and frozen or chilled storage.